Iranian EFL Teachers’ Perceptions of a Digital Literacy-Based Teacher Education - Mokhtari, Abolfazl; Askari, Mohammad Iman; Fatehi Rad , Neda (KMAN Counseling & Psychology Nexus, 2025)
Digital literacy has become increasingly important in today's world due to the widespread use of technology and the internet in various aspects of life. Digital literacy enables teachers to access, evaluate, and use information effectively from various online sources. The mission of the present study was exploring how Iranian EFL teachers perceive a digital literacy-based teacher education. To this end, a grounded theory design was used. The participants taking part in this research included 50 males and females Iranian EFL teachers, holding B.A., M.A. and Ph.D. in TEFL, English Language and Literature, and English Translation fields, with varying years of teaching experience in schools and institutes of Iran. They were picked up through available sampling from virtual groups in social networks. To collect the data, semi-structured interview and audio-reflective journal were used. Data analysis was conducted through the qualitative manual thematic analysis. The following themes were outcomes of data analysis: Digital Information Searching, Digital Interaction, Digital Information Sharing, Digital Collaboration, Digital Content Creation, Familiarity with Soft Wares and Hard Wares, Digital Problem-Solving, Using Word and PowerPoint Skills, General Computer Skills, Using Technology for Educational Purposes, Protecting Digital Devices, Protecting Digital Content, Identifying Digital Needs, and Creative Use of Digital Technologies. EFL teacher educators, administers, authorities and teachers can take useful insights from the results.